How to: pinyon pine & juniper - Colorado State Forest Service, author (Colorado State University. Libraries, 2012)
The brochure offers information on the management and treatment of burned pinyon pine and juniper trees on private property.
Keywords: juniper; fire injury; management decisions; survivability; pinyon pine; fire damage